Multilingual Validation of the Questionnaire for Verifying Stroke-Free Status in West Africa. Issue 1 (January 2016) - Sarfo, Fred; Gebregziabher, Mulugeta; Ovbiagele, Bruce; Akinyemi, Rufus; Owolabi, Lukman; Obiako, Reginald; Akpa, Onoja; Armstrong, Kevin; Akpalu, Albert; Adamu, Sheila; Obese, Vida; Boa-Antwi, Nana; et al.
Abstract : Background and Purpose—: The Questionnaire for Verifying Stroke-Free Status (QVSFS), a method for verifying stroke-free status in participants of clinical, epidemiological, and genetic studies, has not been validated in low-income settings where populations have limited knowledge of stroke symptoms. We aimed to validate QVSFS in 3 languages, Yoruba, Hausa and Akan, for ascertainment of stroke-free status of control subjects enrolled in an on-going stroke epidemiological study in West Africa. Methods—: Data were collected using a cross-sectional study design where 384 participants were consecutively recruited from neurology and general medicine clinics of 5 tertiary referral hospitals in Nigeria and Ghana. Ascertainment of stroke status was by neurologists using structured neurological examination, review of case records, and neuroimaging (gold standard). Relative performance of QVSFS without and with pictures of stroke symptoms (pictograms) was assessed using sensitivity, specificity, positive predictive value, and negative predictive value. Results—: The overall median age of the study participants was 54 years and 48.4% were males. Of 165 stroke cases identified by gold standard, 98% were determined to have had stroke, whereas of 219 without stroke 87% were determined to be stroke-free by QVSFS. Negative predictive value of the QVSFS across the 3 languages was 0.97 (range, 0.93–1.00), sensitivity, specificity, and positive predictive value were 0.98, 0.82, and 0.80, respectively. Agreement between the questionnaire with and without the pictogram was excellent/strong with Cohen k=0.92. Conclusions—: QVSFS is a valid tool for verifying stroke-free status across culturally diverse populations in West Africa. Abstract : Supplemental Digital Content is available in the text.